Graphene oxide coated nano-lithium cobalt oxide positive electrode material and preparation method
By using graphene oxide coating during the hydrothermal synthesis of lithium nanocobalt oxide, the problem of unstable circulation performance of the cathode material of nanocobalt oxide is solved, and better electrochemical performance and rate performance are achieved.
Patent Information
- Application Number
- CN202211566234.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-07
AI Technical Summary
During the circulation process, nano-Cobalt oxide cathode material has problems such as surface side reaction, structural degradation and electrolyte decomposition, resulting in unstable circulation performance and degradation of performance when the particle size is less than 15nm after nano-scaling.
By using graphene oxide to coat during the hydrothermal synthesis of nanocobalt oxide, the nano size and hydrothermal temperature time are adjusted, in-situ coating is achieved, surface side reactions are suppressed, and the circulation stability and electrochemical performance of the material are improved. .
It effectively stabilizes the material morphology and crystal structure, reduces the side reaction between the electrolyte and the material, improves the migration ability of lithium ions, and improves the cycle stability and rate performance of the battery.
Smart Images

Figure CN116161709B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode material preparation, and specifically relates to a graphene oxide-coated nano-lithium cobalt oxide positive electrode material and a preparation method thereof. Background Art
[0002] As human society continues to progress and develop, the energy structure on which people depend for survival is also changing. Coal, oil, and natural gas are becoming increasingly depleted, and the earth's environmental pollution problem is becoming more and more serious. Therefore, we urgently need to find a green and renewable energy source to replace traditional mineral energy. Compared with new energy sources such as solar energy, wind energy, and geothermal energy, chemical power sources can store electrical energy in the form of chemical energy and convert it into electrical energy for use when people need it. As an important green electrical energy storage medium, lithium-ion secondary batteries have become a research hotspot in recent years. In the composition of lithium-ion secondary batteries, the positive electrode material plays an important role, and its performance is the guarantee of key factors such as battery energy density and safety. Compared with other positive electrode materials, lithium cobalt oxide has a simple preparation process, stable operating voltage, high compaction density, and has a capacity of 274mAh g -1 Due to its high theoretical specific capacity, it is widely used in portable electronic products.
[0003] However, conventional lithium cobalt oxide is limited by surface side reactions, surface oxygen loss, structural degradation, electrolyte decomposition and other problems during the charge and discharge process, and its cycle performance is seriously affected. In addition, ordinary micron-sized lithium cobalt oxide has a long lithium ion diffusion path and cannot meet the requirements of fast charge and discharge. Therefore, nano-sizing lithium cobalt oxide is one of the commonly used modification methods. Its main purpose is to shorten the diffusion path of lithium ions and electrons by reducing the particle size of the material, thereby improving the overall lithium ion and electron conductivity of the material. On the other hand, nano-sized electrode materials are conducive to forming full contact with the electrolyte, which is conducive to the release of its specific capacity and the improvement of its rate performance. Zhu et al. studied the transport of lithium ions in nano-lithium cobalt oxide positive electrodes by conductive atomic force microscopy (C-AFM). The results showed that nano-sizing not only shortens the diffusion path of lithium ions, but also its nanocrystalline interface is conducive to the rapid transport of lithium ions.
[0004] Although nano-lithium cobalt oxide shortens the diffusion distance of lithium ions, due to the increase in specific surface area, its contact with the electrolyte will be more sufficient, and the corresponding surface side reactions will be more serious. Therefore, although nano-lithium cobalt oxide can show good rate performance, its cycle stability may be reduced. Okubo et al. prepared lithium cobalt oxide nanocrystals with a particle size of tens of nanometers by hydrothermal method. The results showed that the cycle stability of nano-lithium cobalt oxide deteriorated, and when its particle size was less than 15nm, it was no longer suitable for positive electrode materials. Therefore, it is particularly important to ensure the cycle stability of lithium cobalt oxide on the basis of nano-scale. Surface coating is one of the most effective modification methods for electrode materials. By surface coating the active material, not only can its material morphology and crystal structure be stabilized to a certain extent, but also the occurrence of surface side reactions can be effectively inhibited by changing the physical and chemical state of the surface of the active material, thereby improving the cycle performance of the battery. Summary of the invention
[0005] In view of the above-mentioned problems of nano-lithium cobalt oxide positive electrode, the present invention coats graphene oxide during the hydrothermal synthesis process of nano-lithium cobalt oxide, and adopts a hydrothermal synthesis method to obtain a nano-lithium cobalt oxide positive electrode material with good electrochemical performance.
[0006] To achieve the above-mentioned purpose of the invention, the technical solution of the present invention is as follows:
[0007] A method for preparing a graphene oxide-coated nanoscale lithium cobalt oxide positive electrode material comprises the following steps:
[0008] (1) dissolving a cobalt metal salt in 100 mL of deionized water and stirring at room temperature for 5 to 10 minutes until the metal salt is completely dissolved to obtain a cobalt salt aqueous solution;
[0009] (2) under stirring conditions, adding 100 mL of a 2.5-5 mol / L alkaline solution to a cobalt salt aqueous solution, stirring for 5-10 minutes, adding deionized water to dilute, and stirring in air for 12-18 hours to obtain nano-cobalt hydroxide;
[0010] (3) After the nano-cobalt hydroxide CoOOH in step (2) is centrifuged, purified and dried, 2 mmol of CoOOH and 30 mL of a certain concentration of LiOH aqueous solution are weighed and added to a polytetrafluoroethylene liner, and then 6 mg of graphene oxide sheets after ultrasonic dispersion treatment are added to obtain a reaction precursor;
[0011] (4) The reaction precursor in step (3) is subjected to an oven hydrothermal reaction for a period of time and then cooled to room temperature, the upper clear liquid is sucked out, and the lower precipitate is taken out and centrifuged and dried to obtain the final product.
[0012] As a preferred embodiment, the cobalt salt used in step (1) is one of cobalt acetate, cobalt sulfate, cobalt nitrate and cobalt chloride.
[0013] As a preferred embodiment, the concentration of the aqueous cobalt salt solution in step (1) is 0.4 mol / L.
[0014] As a preferred embodiment, the base used in step (2) is one of lithium hydroxide, sodium hydroxide, potassium hydroxide and ammonia water, and the solution used is an aqueous solution.
[0015] As a preferred embodiment, the concentration of the LiOH aqueous solution prepared in step (3) is 0.1 mol / L, 1 mol / L, or 5 mol / L.
[0016] As a preferred embodiment, the hydrothermal reaction temperature in step (4) is 120-170° C., and the reaction time is 9-12 hours.
[0017] The present invention also provides a nano-scale lithium cobalt oxide positive electrode material coated with graphene oxide obtained by the preparation method.
[0018] The principle of the preparation method of the present invention is as follows: by coating graphene oxide during the hydrothermal synthesis of nano-lithium cobalt oxide, in-situ coating during the formation of nanocrystals can be achieved. By synthesizing at a specific hydrothermal temperature and time, the nano size can be regulated to achieve a better coating effect, inhibit the occurrence of surface side reactions, and improve cycle stability.
[0019] The beneficial effects of the present invention are as follows: through the surface layer formed by graphene oxide on the positive electrode material, its material morphology and crystal structure are stabilized to a certain extent, the side reaction effects with the electrolyte are effectively reduced, and at the same time, the contact state of the electrode and the electrolyte interface is improved, which is beneficial to the migration of lithium ions at the electrode-electrolyte interface and improves its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a transmission electron microscope image of graphene oxide (GO) coated nano-lithium cobalt oxide prepared in Example 1 of the present invention.
[0021] Figure 2 The X-ray powder diffraction patterns of Examples 1-5 and Comparative Example 1 in the present invention are shown.
[0022] Figure 3 It is a comparison diagram of the electrochemical impedance spectra of Example 1 and Comparative Example 1 in the present invention.
[0023] Figure 4 The graph is a variation of the discharge specific capacity of Examples 1-5 and Comparative Example 1 at 1C with the number of cycles.
[0024] Figure 5 It is a comparison chart of the discharge specific capacity of Example 1 and Comparative Example 1 in the present invention at different current densities. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] The embodiment provides a method for preparing a nanoscale lithium cobalt oxide positive electrode material coated with graphene oxide, comprising the following steps:
[0027] (1) dissolving 0.04 mol of a cobalt metal salt into 100 mL of a deionized water solution, stirring at room temperature for 5 to 10 minutes until the metal salt is completely dissolved, to obtain a cobalt salt aqueous solution; the cobalt salt used in step (1) is one of cobalt acetate, cobalt sulfate, cobalt nitrate, and cobalt chloride.
[0028] (2) Under stirring conditions, 100 mL of an alkaline solution with a concentration of 2.5 to 5 mol / L is added to a cobalt salt aqueous solution, stirred for 5 to 10 minutes, and then deionized water is added to dilute the solution and stirred in air for 12 to 18 hours to obtain nano-cobalt hydroxide; the alkali used in step (2) is one of lithium hydroxide, sodium hydroxide, potassium hydroxide and ammonia water, and the solution used is an aqueous solution.
[0029] (3) After the nano-cobalt hydroxide CoOOH in step (2) is centrifuged, purified and dried, 2 mmol of CoOOH and 30 mL of a certain concentration of LiOH aqueous solution are weighed and added to a polytetrafluoroethylene liner, and then 6 mg of graphene oxide sheets after ultrasonic dispersion treatment are added to obtain a reaction precursor; the concentration of the prepared LiOH aqueous solution is 0.1 mol / L, 1 mol / L, and 5 mol / L.
[0030] (4) The reaction precursor in step (3) is subjected to an oven hydrothermal reaction for a period of time and then cooled to room temperature, the upper clear liquid is sucked out, and the lower precipitate is centrifuged and dried to obtain the final product. The hydrothermal reaction temperature is 120-170° C. and the reaction time is 9-12 hours.
[0031] Example 1
[0032] (1) Dissolve 0.04 mol of cobalt nitrate in 100 mL of deionized water and stir at room temperature for 8 minutes to obtain a cobalt nitrate aqueous solution (light purple clear liquid);
[0033] (2) under stirring conditions, 100 mL of a 3 mol / L sodium hydroxide solution was added to the cobalt nitrate aqueous solution, stirred for 8 minutes, and then 1800 mL of deionized water was added and stirred in air for 15 hours to obtain nano cobalt hydroxide (CoOOH);
[0034] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 6mg graphene oxide, 30mL, 1mol / L LiOH aqueous solution, and add them together into the lining of the reactor to obtain a reaction precursor;
[0035] (4) reacting the reaction precursor in step (3) in a reactor in a high-temperature oven at 170° C. for 12 h, then naturally cooling to room temperature, aspirating the upper clear liquid, taking the lower precipitate and centrifuging and drying to obtain the final product;
[0036] Example 2
[0037] (1) Dissolve 0.04 mol of cobalt chloride in 100 mL of deionized water and stir at room temperature for 5 minutes to obtain a cobalt chloride aqueous solution (light purple clear liquid);
[0038] (2) under stirring conditions, 100 mL of a 5 mol / L potassium hydroxide solution was added to the cobalt chloride aqueous solution, stirred for 10 minutes, and then 1800 mL of deionized water was added and stirred in air for 15 hours to obtain nano cobalt hydroxide (CoOOH);
[0039] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 6mg graphene oxide, 30mL, 1mol / L LiOH aqueous solution, and add them together into the lining of the reactor to obtain a reaction precursor;
[0040] (4) reacting the reaction precursor in step (3) in a reactor in a high-temperature oven at 150° C. for 12 h, then naturally cooling to room temperature, aspirating the upper clear liquid, taking the lower precipitate and centrifuging and drying to obtain the final product;
[0041] Example 3
[0042] (1) Dissolve 0.04 mol of cobalt sulfate in 100 mL of deionized water and stir at room temperature for 10 minutes to obtain a cobalt sulfate aqueous solution (light purple clear liquid);
[0043] (2) under stirring conditions, 100 mL of a 3 mol / L sodium hydroxide solution was added to the cobalt sulfate aqueous solution, stirred for 5 minutes, and then 1800 mL of deionized water was added and stirred in air for 12 hours to obtain nano cobalt hydroxide (CoOOH);
[0044] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 6mg graphene oxide, 30mL, and 5mol / L LiOH aqueous solution and add them together into the lining of the reactor to obtain a reaction precursor;
[0045] (4) reacting the reaction precursor in step (3) in a reactor in a high-temperature oven at 170° C. for 10 h, then naturally cooling to room temperature, aspirating the upper clear liquid, taking the lower precipitate and centrifuging and drying to obtain the final product;
[0046] Example 4
[0047] (1) Dissolve 0.04 mol of cobalt nitrate in 100 mL of deionized water and stir at room temperature for 8 minutes to obtain a cobalt nitrate aqueous solution (light purple clear liquid);
[0048] (2) under stirring conditions, 100 mL of a 2.5 mol / L lithium hydroxide solution was added to the cobalt nitrate aqueous solution, stirred for 10 minutes, and then 1800 mL of deionized water was added and stirred in air for 18 hours to obtain nano cobalt hydroxide (CoOOH);
[0049] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 6mg graphene oxide, 30mL, and 5mol / L LiOH aqueous solution and add them together into the lining of the reactor to obtain a reaction precursor;
[0050] (4) reacting the precursor in step (3) in a reactor in a high-temperature oven at 120° C. for 9 h, then naturally cooling to room temperature, aspirating the upper clear liquid, taking the lower precipitate and centrifuging and drying to obtain the final product;
[0051] Example 5
[0052] (1) Dissolve 0.04 mol of cobalt sulfate in 100 mL of deionized water and stir at room temperature for 5 minutes to obtain a cobalt sulfate aqueous solution (light purple clear liquid);
[0053] (2) under stirring conditions, 100 mL of 5 mol / L ammonia water was added to the cobalt sulfate aqueous solution, stirred for 5 minutes, and then 1800 mL of deionized water was added and stirred in air for 18 hours to obtain nano cobalt hydroxide (CoOOH);
[0054] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 6mg graphene oxide, 30mL, and 0.1mol / L LiOH aqueous solution and add them together into the inner lining of the reactor to obtain a reaction precursor;
[0055] (4) reacting the reaction precursor in step (3) in a reactor in a high-temperature oven at 170° C. for 12 h, then naturally cooling to room temperature, aspirating the upper clear liquid, taking the lower precipitate and centrifuging and drying to obtain the final product;
[0056] Example 6
[0057] (1) Dissolve 0.04 mol of cobalt acetate in 100 mL of deionized water and stir at room temperature for 8 minutes to obtain a cobalt acetate aqueous solution (light purple clear liquid);
[0058] (2) under stirring conditions, 100 mL of a 5 mol / L potassium hydroxide solution was added to the cobalt acetate aqueous solution, stirred for 10 minutes, and then 1800 mL of deionized water was added and stirred in air for 15 hours to obtain nano cobalt hydroxide (CoOOH);
[0059] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 6mg graphene oxide, 30mL, and 0.1mol / L LiOH aqueous solution and add them together into the inner lining of the reactor to obtain a reaction precursor;
[0060] (4) The reaction precursor in step (3) was reacted in a reactor in a high-temperature oven at 150° C. for 12 h and then naturally cooled to room temperature. The upper clear liquid was aspirated, and the lower precipitate was centrifuged and dried to obtain the final product.
[0061] Comparative Example 1
[0062] (1) Dissolve 0.04 mol of cobalt nitrate in 100 mL of deionized water and stir at room temperature for 8 minutes to obtain a cobalt nitrate aqueous solution (light purple clear liquid);
[0063] (2) under stirring conditions, 100 mL of a 3 mol / L sodium hydroxide solution was added to the cobalt nitrate aqueous solution, stirred for 8 minutes, and then 1800 mL of deionized water was added and stirred in air for 15 hours to obtain nano cobalt hydroxide (CoOOH);
[0064] (3) Centrifuge and purify the nano-CoOOH in step (2) and dry it. Take 2mmol CoOOH, 30mL, and 1mol / L LiOH aqueous solution and add them together into the lining of the reactor to obtain a reaction precursor;
[0065] (4) reacting the reaction precursor in step (3) in a reactor in a high-temperature oven at 170° C. for 12 h, then naturally cooling to room temperature, aspirating the upper clear liquid, taking the lower precipitate and centrifuging and drying to obtain the final product;
[0066] The nano-lithium cobalt oxide coated with graphene oxide obtained in Example 1 was observed by transmission electron microscopy. Figure 1 ; Figure 2 X-ray powder diffraction patterns of nano-lithium cobalt oxide coated with graphene oxide in Examples 1-5 and nano-lithium cobalt oxide in Comparative Example 1; Figure 3This is a comparison diagram of the electrochemical impedance spectra of Example 1 and Comparative Example 1. After the coating treatment, the intrinsic resistance and charge transfer resistance of the nano-lithium cobalt oxide positive electrode material are reduced.
[0067] Figure 4 The results of Examples 1-5 and Comparative Example 1 at 1C (1C = 150 mAh g -1 ) as a function of the number of cycles. After 100 cycles, the discharge capacities of Examples 1-5 and Comparative Example 1 were 76.1, 68.7, 65.1, 62.8, 61.1 and 44.3 mAh g, respectively. -1 , the capacity retention rates were 59.8%, 53.9%, 52.2%, 49.3%, 48.9% and 35.1% respectively. It can be seen that the capacity retention rate of nano-lithium cobalt oxide coated with graphene oxide can effectively improve the cycle capacity retention rate at 1C current density. Figure 5 The figure is a comparison of the discharge specific capacities of Example 1 and Comparative Example 1 at different current densities. It can be seen that the discharge specific capacities of Example 1 at different current densities are higher than those of Comparative Example 1, especially at 10C. By comparing the specific capacities at different currents before and after coating, it can be concluded that the coated material has a more excellent rate performance.
[0068] In summary, the present invention provides a graphene oxide-coated nano-lithium cobalt oxide positive electrode material and a preparation method thereof. By coating graphene oxide during the hydrothermal synthesis process of nano-lithium cobalt oxide, in-situ coating during the formation of nanocrystals is achieved. Synthesis is performed at a specific hydrothermal temperature and time, and the nano size can be regulated to achieve a better coating effect. The cyclic stability performance of the embodiment shows that graphene oxide as a coating layer can effectively inhibit the occurrence of side reactions between nano-lithium cobalt oxide and the electrolyte, and improve the structural stability. On the other hand, improving the contact state of the electrode and electrolyte interface is conducive to the migration of lithium ions at the electrode electrolyte interface, thereby also improving its rate performance.
Claims
1. A method for preparing a graphene oxide-coated nanoscale lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: (1) dissolving a cobalt metal salt in 100 mL of deionized water and stirring at room temperature for 5 to 10 minutes until the metal salt is completely dissolved to obtain a cobalt salt aqueous solution; (2) under stirring conditions, adding 100 mL of a 2.5-5 mol / L alkaline solution to a cobalt salt aqueous solution, stirring for 5-10 minutes, adding deionized water to dilute, and stirring in air for 12-18 hours to obtain nano-cobalt hydroxide; (3) After the nano-cobalt hydroxide CoOOH in step (2) is centrifuged, purified and dried, 2 mmol of CoOOH and 30 mL of a certain concentration of LiOH aqueous solution are weighed and added to a polytetrafluoroethylene liner, and then 6 mg of graphene oxide sheets after ultrasonic dispersion treatment are added to obtain a reaction precursor; (4) The reaction precursor in step (3) is subjected to an oven hydrothermal reaction for a period of time and then cooled to room temperature, the upper clear liquid is sucked out, and the lower precipitate is centrifuged and dried to obtain the final product; the hydrothermal reaction temperature in step (4) is 120 to 170° C., and the reaction time is 9 to 12 hours.
2. The method for preparing a graphene oxide-coated nanoscale lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The cobalt salt used in step (1) is one of cobalt acetate, cobalt sulfate, cobalt nitrate and cobalt chloride.
3. The method for preparing a graphene oxide-coated nanoscale lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The concentration of the cobalt salt aqueous solution in step (1) is 0.4 mol / L.
4. The method for preparing a graphene oxide-coated nanoscale lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The alkali used in step (2) is one of lithium hydroxide, sodium hydroxide, potassium hydroxide and ammonia water, and the solution used is an aqueous solution.
5. The method for preparing a graphene oxide-coated nanoscale lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The concentration of the LiOH aqueous solution prepared in step (3) is 0.1 mol / L, 1 mol / L, and 5 mol / L.
6. A nanoscale lithium cobalt oxide positive electrode material coated with graphene oxide obtained by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method for producing graphene-coated lithium iron phosphate
CN102544516A
Efficient graphene coated lithium cobalt oxide battery cathode material and preparation method thereof
CN104064771A
